2022
DOI: 10.3389/fphys.2022.922037
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ferulic acid supplementation improved cottonseed meal-based diet utilization by enhancing intestinal physical barrier function and liver antioxidant capacity in grass carp (Ctenopharyngodon Idellus)

Abstract: The present study explored the effects of ferulic acid (FA) supplementation in cottonseed meal (CSM)-based diets on grass carp growth performance, feed utilization, liver antioxidation status, and intestinal physical barrier function. Here, four experimental diets supplemented with FA at graded levels (0, 50, 100 and 200 mg/kg) and CSM as the main protein source (384.6 g/kg feed) for an 8-week feeding trial. Our results indicated that 200 mg/kg FA supplementation in a CSM-based diet significantly improved grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…(2022) reported that dietary 200 to 800 mg/kg protease supplementation could significantly decrease the contents of AST and ALT in red swamp crayfish Procambarus clarkia fed plant-based diets. Blood ALT and AST are crucial indicators of liver injury in aquatic animals, and their low levels always indicate liver health ( Chen et al., 2021 , 2022a , 2022b ). The aforementioned findings substantiated the assertion that the incorporation of protease in LFD exerted a hepatoprotective effect on aquatic animals.…”
Section: Effects Of Protease Application On Aquatic Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) reported that dietary 200 to 800 mg/kg protease supplementation could significantly decrease the contents of AST and ALT in red swamp crayfish Procambarus clarkia fed plant-based diets. Blood ALT and AST are crucial indicators of liver injury in aquatic animals, and their low levels always indicate liver health ( Chen et al., 2021 , 2022a , 2022b ). The aforementioned findings substantiated the assertion that the incorporation of protease in LFD exerted a hepatoprotective effect on aquatic animals.…”
Section: Effects Of Protease Application On Aquatic Animalsmentioning
confidence: 99%
“…While LFD and PSD have been recognized to offer cost-saving advantages and reduce dependence on fishmeal, studies have also linked them to adverse effects on fish and shrimp ( Panigrahi et al., 2019 ; Willora et al., 2022 ). Currently, plant-based proteins dominate fishmeal substitution in aquafeed ( Chen et al., 2022a , 2022b ); however, these proteins have several drawbacks, including anti-nutritional factors (ANFs), low digestibility, poor bioavailability, and palatability issues ( Shomorin et al., 2019 ). Previous research has indicated that diets incorporating plant proteins may impede the activity of digestive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Cottonseed meal (CSM) is a protein-rich product that can be found in large quantities and is typically more cost-effective compared to other protein sources such as fish meal (FM) and soybean meal (SBM) [ 14 16 ]. However, deepening researches have revealed that CSM especially the gossypol residue contained in CSM could cause severe intestinal inflammation and gut barrier injury in diverse monogastric animals such as fishes and livestock [ 13 , 17 24 ]. Try to decrease the remaining gossypol in CSM is one of the important strategy to eliminate the deleterious effects [ 25 , 26 ], but it depends on the dephenolization process which may cause extra cost.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigating the growth inhibition and oxidative stress induced by CSM diets can be achieved through chemical detoxification, microbial fermentation, or supplementation with green additives, as previously demonstrated in juvenile grass carps (Ctenopharyngodon idellus) [12], Nile tilapia (Oreochromis niloticus) [13], and channel catfish (Ictalurus punctatus) [14]. Among these methods, chemical detoxification by adding FeSO 4 to the CSM detoxification process has been widely adopted due to its cost-effectiveness, simplicity, and efficacy.…”
Section: Introductionmentioning
confidence: 99%